The addition of a goal-based motivational interview to treatment as usual to enhance engagement and reduce dropouts in a personality disorder treatment service: results of a feasibility study for a randomized controlled trial - McMurran, Mary; Cox, W. Miles; Whitham, Diane; Hedges, Lucy (BioMed Central, 2013)
Background: There are high rates of treatment non-completion for personality disorder and those who do not complete treatment have poorer outcomes. A goal-based motivational interview may increase service users’ readiness to engage with therapy and so enhance treatment retention. We conducted a feasibility study to inform the design of a randomized controlled trial. The aims were to test the feasibility of recruitment, randomization and follow-up, and to conduct a preliminary evaluation of the effectiveness of the motivational interview. Methods: Patients in an outpatient personality disorder service were randomized to receive the Personal Concerns Inventory plus treatment as usual or treatment as usual only. The main randomized controlled trial feasibility criteria were recruitment of 54% of referrals, and 80% of clients and therapists finding the intervention acceptable. Information was collected on treatment attendance, the clarity of therapy goals and treatment engagement. Results: The recruitment rate was 29% (76 of 258). Of 12 interviewed at follow-up, eight (67%) were positive about the Personal Concerns Inventory. Pre-intervention interviews were conducted with 61% (23 out of 38) of the Personal Concerns Inventory group and 74% (28 out of 38) of the treatment as usual group. Participants’ therapy goals were blind-rated for clarity on a scale of 0 to 10. The mean score for the Personal Concerns Inventory group was 6.64 (SD = 2.28) and for the treatment as usual group 2.94 (SD = 1.71). Over 12 weeks, the median percentage session attendance was 83.33% for the Personal Concerns Inventory group (N = 17) and 66.67% for the treatment as usual group (N = 24). Of 59 eligible participants at follow-up, the Treatment Engagement Rating scale was completed for 40 (68%). The mean Treatment Engagement Rating scale score for the Personal Concerns Inventory group was 6.64 (SD = 2.28) and for the treatment as usual group 2.94 (SD = 1.71). Of the 76 participants, 63 (83%) completed the Client Service Receipt Inventory at baseline and 34 of 59 (58%) at follow-up. Conclusion: Shortfalls in recruitment and follow-up data collection were explained by major changes to the service. However, evidence of a substantial positive impact of the Personal Concerns Inventory on treatment attendance, clarity of therapy goals and treatment engagement, make a full-scale evaluation worth pursuing. Further preparatory work is required for a multisite trial.